Pengembangan e-modul ajar berbasis kearifan lokal untuk meningkatkan pengetahuan murid SMP di Togean - Gunawan Gunawan; Rizal Rizal; Hendriana Sri Rejeki (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
This research aims to develop a teaching e-module based on local wisdom that can increase students' knowledge about healthy and nutritious balanced food. The research uses the Research and Development (R&D) method with the ADDIE model which includes five stages, namely analysis, design, development, implementation, and evaluation. The research subjects amounted to 32 students in grade VII of SMP Negeri 1 Togean. The development results show that the e-module is prepared using the Canva application with a structure consisting of an introduction, content, and closing/attachment, and is equipped with an interactive barcode feature that facilitates access through digital devices that can directly access e-materials, LKPD, Formative and Summative Exams. The results of the feasibility validation showed that the average score of the media expert was 3.75 (very feasible), the content expert 3.78 (very feasible), and the nutritionist was 3.07 (feasible). Field trials also showed excellent results, with an average score of 4.00 (very feasible) on a small scale and 3.99 (very feasible) on a large scale. Then from the results of the learning test, there was a significant increase from the initial average score of 49.53 with 25% completeness, to a final score of 95.00 with 100% completeness after the use of the e-module. Thus, this teaching e-module based on Togean local wisdom is considered valid, practical, and effective to increase students' knowledge in PJOK learning, especially in healthy and nutritious balanced food materials.